A Design of a Consignment Information System - Sugiarno, Bayu; Mukhoyyaroh, Khurin 'ien; Yazid, Ahmad Subhan; son, Sumarsono (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
UD. BTECH Indonesia is a company which worked in the marketing service scope/division of computer accesories. The recording of goods income and otcome still uses manual system especially in the warehouse division, because it is only the author to check the goods stock. The purpose of this research is to analyze the system which has been exixting and to develop the consigned information in UD. BTECH. This system tries to connecting the company with the suppliers and consumers. The software development model uses waterfall model, whereas for the data model uses structured model, Entity Relation Diagram (ERD) to describe the data model and Data Flow Diagram (DFD) to imagine the functional model. The system is implemented by using the PHP programming language and MySQL database. The application that has made is expected to help and support the marketing system that already exist. The results of this final task/ research paper is an analysis on the existing system and consignment information system in UD.BTECH that is used to the marketing record, marketing consignment purchasing, purhasing consignment, marketing returns and preparing report.